Exploring Haskell: Higher-order Functions

Higher-order functions allow common programming patterns to be encapsulated as functions.

Basic Concepts

A function that takes a function as an argument or returns a function as a result is called a higher-order function. Because the term curried already exists for returning functions as results, the term higher-order is often just used for taking functions as arguments.

twice :: (a -> a-> a -> a
twice f x = f (f x)
 
twice (*23 -- 12
twice reverse [1,2,3-- [1,2,3]

Processing Lists

The standard library defines a number of useful higher-order functions for processing lists.

map :: (a -> b-> [a-> [b]
map f xs = [ f x | x <- xs ]
----
map :: (a -> b-> [a-> [b]
map f []= []
map f (x:xs= f x : map f xs
----
map (+1) [1,3,5,7-- [2,4,6,8]
 
map even [1,2,3,4-- [False,True,False,True]
 
map reverse ["abc","def","ghi"-- ["cba","fed","ihg"]
----
map (map (+1)) [[1,2,3],[4,5]] -- { applying the outer map }
[map (+1) [1,2,3], map (+1) [4,5]] -- { applying the inner maps }
[[2,3,4],[5,6]]
filter :: (a -> Bool-> [a-> [a]
filter p xs = [ x | x <- xs, p x ]
----
filter :: (a -> Bool-> [a-> [a]
filter p [] = []
filter p (x : xs| p x       = x : filter p xs
                  | otherwise = filter p xs
----
filter even [1..10-- [2,4,6,8,10]
 
filter (> 5) [1..10-- [6,7,8,9,10]
 
filter (/= ' '"abc def ghi" -- "abcdefghi"
all even [2,4,6,8-- True
----
any odd [2,4,6,8-- False
----
takeWhile even [2,4,6,7,8-- [2,4,6]
----
dropWhile odd [1,3,5,6,7-- [6,7]

The foldr Function

Many functions that take a list as their argument can be defined using the following pattern of recursion on lists:

f []     = v
f (x:xs= x # f xs

The function maps the empty list to a value v, and any non-empty list to an operator # applied to the head of the list and the result of recursively processed tail.

For example:

sum []       = 0
sum (x : xs= x + sum xs
----
product []       = 1
product (x : xs= x * product xs
----
or []       = False
or (x : xs= x || or xs
----
and []       = True
and (x : xs= x && and xs

The higher-order library function foldr (fold right) encapsulates this pattern of recursion for defining functions on lists.

Fold right function assumes that the given operator associates to the right: 1+(2+(3+0)).

foldr :: (a -> b -> b-> b -> [a-> b
foldr f v []       = v
foldr f v (x : xs= f x (foldr f v xs)
----
sum :: Num a => [a-> a
sum = foldr (+) 0
----
product :: Num a => [a-> a
product = foldr (*) 1
----
or :: [Bool-> Bool
or = foldr (||) False
----
and :: [Bool-> Bool
and = foldr (&&) True

It is easier to reason about foldr f v in a non-recursive way, as simply replacing each : (cons) operator in a list by the function f, and the empty list at the end by the value v.

For example, applying the function foldr (+) 0 to the list 1 : (2 : (3 : [])) gives the result 1 + (2 + (3 + 0)) in which : and [] have been replaced by + and 0.

A quick reminder: [1,2,3] and 1 : (2 : (3 : [])) are equivalent.

Many functions can be redefined with foldr:

length :: [a-> Int
length []       = 0
length (_ : xs= 1 + length xs
----
length [1,2,3]
1 : (2 : (3 : []))
1 + (1 + (1 + 0))
3
----
length :: [a-> Int
length = foldr (\_ n -> 1 + n0
 
----
 
reverse :: [a-> [a]
reverse []       = []
reverse (x : xs= reverse xs ++ [x]
 
reverse [1,2,3]
1 : (2 : (3 : []))
(([] ++ [3]) ++ [2]) ++ [1]
----
snoc x xs = xs ++ [x-- cons backwards
 
reverse :: [a-> [a]
reverse = foldr snoc []

The foldl Function

Opposite of foldr, assumes that operator associates to the left: ((0+1)+2)+3.

foldl :: (a -> b -> a-> a -> [b-> a
foldl f v []       = v
foldl f v (x : xs= foldl f (f v xxs

It is useful for mapping the empty list to the accumulator value v, and any non-empty list to the result of recursively processing the tail using a new accumulator value obtained by applying an operator # to the current value and the head of the list.

f v []     = v
f v (x:xs= f (v # xxs

When a function can be defined using both foldr and foldl the choice of which definition is preferable is usually based on efficiency and requires considering the evaluation mechanism of Haskell.

The Composition Operator

The standard operator . returns the composition of two functions as a single function.

(.) :: (b -> c-> (a -> b-> (a -> c)
f . g = \x -> f (g x)
----
odd n = not (even n)
odd = not . even
----
twice f x = f (f x)
twice = f . f
----
id :: a -> a
id = \x -> x
-- compose a list of functions
compose :: [a -> a-> (a -> a)
compose = foldr (.) id

Continuing later on.

View Other Posts